Balance of propulsive forces - Kleshnev, V. (BioRow, 2019)
In this newsletter I continue analysis of forces in rowing, and focus here on the balance of propulsive forces. The force Fbx acting on boat was previously defined (RBN 2019/01) as the difference between the pin Fpx and stretcher forces Fsx: Fbx = Fpx - Fsx (1)